Gap Analysis Between The Implementation of Operational Level Environmental Management Systems and Integrated Green Supply Chain Management Practices - Putu Widya Purnama Dewi; I Made Gunamantha; Dewa Made Atmaja (Jurnal Penelitian Pendidikan IPA, 2026)
Environmental Management Systems (EMS) have been widely implemented to improve organizational environmental performance; however, their integration with Green Supply Chain Management (GSCM) remains limited, particularly in the seafood processing industry. This study aims to evaluate the gap between operational-level EMS implementation and integrated GSCM practices at PT. IAMBEU Mina Utama while identifying priority improvement areas to strengthen sustainable supply chain performance. A quantitative-evaluative case study approach was employed using the Green Supply Chain Operations Reference (Green SCOR) framework covering the Plan, Source, Make, Deliver, and Return processes. Data were collected through Likert-scale questionnaires, interviews, field observations, and document analysis. Gap analysis and priority assessment based on environmental and operational impacts were applied to determine critical Key Performance Indicators (KPIs). The results show that EMS implementation (4.20) exceeds GSCM implementation (3.89), indicating a moderate integration gap. The largest gaps were identified in the Return, Deliver, and Plan processes, while priority KPIs include waste management monitoring, circular economy implementation, supplier environmental evaluation, transportation emission monitoring, energy efficiency, and production waste management. The findings indicate that although the company has established a strong internal environmental management system, sustainability practices have not been fully integrated across the supply chain. This study contributes to the development of EMS–GSCM integration using the Green SCOR framework and provides practical recommendations to support sustainable supply chain performance in line with the Sustainable Development Goals, particularly SDG 12 (Responsible Consumption and Production).